Characterization of novel phage pK3–24 targeting multidrug-resistant Klebsiella pneumoniae and its therapeutic efficacy in Galleria mellonella larvae - Junxia Feng; Xiaohu Cui; Bing Du; Jinfeng Chen; Guanhua Xue; Lin Gan; Yanling Feng; Zheng Fan; Yuehua Ke; Jinghua Cui; Tongtong Fu; Hanqing Zhao; et al. (Virus Research)
Klebsiella pneumoniae is a common, conditionally pathogenic bacterium that often has a multidrug-resistant phenotype, leading to failure of antibiotic therapies. It can therefore induce serious diseases, including community-acquired pneumonia and bloodstream infections. As an emerging alternative to antibiotics, phages are considered key to solving the problem of drug-resistant bacterial infections. Here, we report a novel phage, pK3–24, that mainly targets ST447 K. pneumoniae. Phage pK3–24 is a T7-like short-tailed phage with a fast adsorption capacity that forms translucent plaques with halos on bacterial lawns. The optimal multiplicity of infection (MOI) is 0.01, and the average burst size is 50 PFU/mL. Phage pK3–24 shows environmental stability, surviving at below 50 °C and at pH values of 6–10. It has a double-stranded DNA genome of 40,327 bp and carries no antibiotic-resistance, virulence, or lysogeny genes. Phylogenetic analysis assigned phage pK3–24 to the genus Przondovirus as a new species. Phage pK3–24 inhibited the production of biofilm. Moreover, treatment with pK3–24 at doses with an MOI > 1 effectively reduced the mortality of Galleria mellonella larvae infected with ST447 K. pneumoniae.